2012
DOI: 10.2134/agronj2011.0213
|View full text |Cite
|
Sign up to set email alerts
|

Corn Hybrid Growth Stage Influence on Crop Reflectance Sensing

Abstract: Active-light crop canopy sensing for corn (Zea mays L.) N fertilizer rate decisions typically include measurements of N-suffi cient plants as a reference. When producers use multiple hybrids in one fi eld, the question is raised of whether an N-suffi cient reference is needed for each hybrid. Th e objective of this research was to assess the impact of suffi ciently N-fertilized, similar-maturing corn hybrids on crop-refl ectance measurements. Eleven similar-maturing hybrids were selected from three sites in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Therefore, when reference strips are used to calibrate sensors, a separate reference strip should be used for each hybrid. Sheridan et al (2012) found that reflectance differences among corn hybrids had a minimal impact on N fertilizer recommendations. On the other hand, Jasper et al (2006) observed that winter wheat inter‐cultivar differences in amber NDVI translates to a misdiagnosis of N uptake by up to 20 kg ha −1 .…”
mentioning
confidence: 99%
“…Therefore, when reference strips are used to calibrate sensors, a separate reference strip should be used for each hybrid. Sheridan et al (2012) found that reflectance differences among corn hybrids had a minimal impact on N fertilizer recommendations. On the other hand, Jasper et al (2006) observed that winter wheat inter‐cultivar differences in amber NDVI translates to a misdiagnosis of N uptake by up to 20 kg ha −1 .…”
mentioning
confidence: 99%
“…Plant population has the potential to affect crop canopy sensor readings and consequently N recommendation rates. However, previous work showed that reflectance differences among hybrids had minimal impact on fertilizer N recommendations (Sheridan et al, 2012), therefore having a reference strip of the same hybrid may not be critical. With this research we explored whether reference strips of differing plant populations are important in the determination of final in‐season N recommendation.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that ISR index values decrease with increased plant growth, while NDVI increases with plant growth. This inverse relationship has been illustrated (Kitchen et al, 2010;Sheridan et al, 2012).…”
Section: Holland-schepersmentioning
confidence: 90%
“…Additionally, these N-sufficient reference areas should avoid areas that are unique or historically have had other management problems (e.g., heavy weed infestation, head-lands with soil compaction, terraces, manure history). While different maize hybrids can have an effect on reflectance measurements of N-sufficient plants, the impact is minimal and will not greatly impact algorithm N rate recommendations (Sheridan et al, 2012). However, experience working with producers has demonstrated that other soil and crop management factors may cause variations in reflectance, so producers are encouraged to have a sufficient-N reference area for each field.…”
Section: University Of Missouri/usda-arsmentioning
confidence: 99%
See 1 more Smart Citation